PENILAIAN PELAKSANAAN USAHA KESEHATAN SEKOLAH DASAR DI KABUPATEN PESISIR SELATAN - Rosmanelli FIK-UNP; Yaslindo FIK-UNP; Kibadra FIK-UNP (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2019)
Some schools still do not carry out UKS activities as they should. Caused by several factors such as a lack of teacher understanding of the implementation of school health business activities (UKS) in elementary schools and the teacher had never attended a socialization of school health business activities (UKS) in elementary schools. The type of this research is quantitative by using descriptive method which aims to determine the Assessment of the Implementation of Primary School Health Enterprises in Pesisir Selatan District (Case Study in Public Elementary Schools). The instrument in this study is the way researchers assess / fill out observation questionnaires / observation sheets that are in accordance with the UKS assessment issued by the Ministry of Health in collaboration with various ministries in the form of cross-sectoral activities so as to cause more objective information from respondents. The sampling technique was carried out by purposive sampling, from 45 primary schools to 30 primary schools (two schools for one sub-district). The results of the study were obtained from the average research responses of each variable from the Evaluation of the Implementation of Primary School Health Enterprises in Pesisir Selatan District (Case Study in Public Elementary Schools) with an achievement rate of 55.72% and including sufficient interpretation.